2007
DOI: 10.3892/ijmm.20.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl pyruvate induces necrosis-to-apoptosis switch and inhibits high mobility group box protein 1 release in A549 lung adenocarcinoma cells

Abstract: Ethyl pyruvate (EP), a stable lipophilic pyruvate derivative, has been shown to exert anti-inflammatory activities through inhibiting the expression of various pro-inflammatory mediators as well as circulating levels of high mobility group box protein 1 (HMGB1) in a variety of in vitro and in vivo model systems. Necrotic cell death triggers an inflammatory response through release of HMGB1 in the extracellular space due to the membrane rupture. In an effort to better understand the pharmacological action mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 27 publications
2
52
0
1
Order By: Relevance
“…50,51 For instance, excess ROS could trigger necrosis in response to metabolic stress and alleviation of ROS production by antioxidants switches the death mode from necrosis to apoptosis. 52,53 In addition, the superoxide generator menadione prevents apoptosis by inactivation of caspases, thus leading to necrosis in HepG2 cells. 54 We observed that oxaliplatin gradually increased ROS level and UDCA could suppress ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 For instance, excess ROS could trigger necrosis in response to metabolic stress and alleviation of ROS production by antioxidants switches the death mode from necrosis to apoptosis. 52,53 In addition, the superoxide generator menadione prevents apoptosis by inactivation of caspases, thus leading to necrosis in HepG2 cells. 54 We observed that oxaliplatin gradually increased ROS level and UDCA could suppress ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…However, in their experiments LDH (a necrotic marker) was also extracellularly released under the stimulation conditions, and the release was correlated with HMGB1 release. Moreover, Lim et al reported that ethyl pyruvate, a stable pyruvate derivative, suppresses the glucose deprivation-induced HMGB1 release from A549 lung adenocarcinoma cells by preventing necrotic cell death and switching cell death mode to apoptosis (23). In addition, Scaffidi et al revealed using HeLa cells that HMGB1 is extracellularly released from necrotic but not apoptotic cells after treatment with various cytotoxic substances (21).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that HMGB1 is extracellularly released from various types of cells accompanied with cell death (18,(21)(22)(23). Thus, we determined whether LPSstimulation also induces apoptotic and/or necrotic cell death in RAW264.7 cells.…”
Section: Effect Of Lps On Hmgb1 Release and Cell Deathmentioning
confidence: 96%
See 1 more Smart Citation
“…Tümör enjeksiyonundan sonra yükselen serum IL6 ve HMGB1 seviyeleri EP tedavisi alan hayvanlarda belirgin olarak azalır [20]. EP A549 akciğer adenokarsinom hücrelerinde nekroz-apopitoz değişimini uyarır ve HMGB1 salınımını inhibe eder [21].…”
Section: Etil Pirüvat (Ep)unclassified